2007
DOI: 10.1681/asn.2007020207
|View full text |Cite
|
Sign up to set email alerts
|

Partial Rescue of Glomerular Laminin α5 Mutations by Wild-Type Endothelia Produce Hybrid Glomeruli

Abstract: Both endothelial cells and podocytes are sources for laminin ␣1 at the inception of glomerulogenesis and then for laminin ␣5 during glomerular maturation. Why glomerular basement membranes (GBM) undergo laminin transitions is unknown, but this may dictate glomerular morphogenesis. In mice that genetically lack laminin ␣5, laminin ␣5␤2␥1 is not assembled, vascularized glomeruli fail to form, and animals die at midgestation with neural tube closure and placental deficits. It was previously shown that renal corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 31 publications
(37 reference statements)
6
35
0
Order By: Relevance
“…Within 5 d after transplantation, sections of the engrafted Col4a3 knockout kidneys contained numerous LacZ-positive, host-derived endothelial cells (Figure 4A). As shown previously, this indicated the formation of hybrid glomeruli within grafts, 6 which in this case contained wildtype endothelial cells and Col4a3 mutant podocytes. When serial sections were incubated with anti-collagen ␣1␣2␣1(IV), most basement membranes within the host kidney as well as within grafts labeled positively, including the immature GBMs found within the host kidney glomeruli and hybrid glomeruli within grafts ( Figure 4B).…”
Section: ␣3␣4␣5(iv) In Hybrid Glomerulisupporting
confidence: 80%
See 4 more Smart Citations
“…Within 5 d after transplantation, sections of the engrafted Col4a3 knockout kidneys contained numerous LacZ-positive, host-derived endothelial cells (Figure 4A). As shown previously, this indicated the formation of hybrid glomeruli within grafts, 6 which in this case contained wildtype endothelial cells and Col4a3 mutant podocytes. When serial sections were incubated with anti-collagen ␣1␣2␣1(IV), most basement membranes within the host kidney as well as within grafts labeled positively, including the immature GBMs found within the host kidney glomeruli and hybrid glomeruli within grafts ( Figure 4B).…”
Section: ␣3␣4␣5(iv) In Hybrid Glomerulisupporting
confidence: 80%
“…Furthermore, quantitative confocal image analysis showed that GBMs that form in these wildtype/ Lama5 mutant glomerular hybrids can contain up to approximately one-half the full complement of laminin ␣5 immunolabel, indicating that substantial amounts of GBM laminin can stem from the endothelium. 6 By contrast, and as shown here, when Alport mouse metanephroi were grafted into wildtype hosts, there was no expression of collagen ␣3␣4␣5(IV) in hybrid glomeruli within grafts, despite the presence of abundant wildtype endothelial cells, indicating once again a strictly podocyte origin for this collagen IV heterotrimer.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations